Doing the Rights Thing Approaches to Human Rights and Campaigning - Spry, Damien (UTS Shopfront Series, 2008)
This book is about the current state of human rights and the advocacy campaigns to end various abuses to these rights. It challenges views that give authority exclusively to the 1948 Universal Declaration of Human Rights, and reductionist views that take the subsequently framed body of international human rights law as sacrosanct suggesting this this is an incomplete and therefore insufficient view of human rights; that the struggle for human rights exists in historical, political and cultural contexts that may variously challenge or lend support to perspectives on human rights. The author presents three accounts to argue the case: a brief historical overview of human rights; a close reading of a key human rights organisation; and accounts from a recent human rights campaign in Australia. These examples suggest that smaller, nimbler campaign organisations, focused on concrete human rights outcomes, can strategically and successfully employ discourses that are designed to fit with the local political and cultural settings.